Improving Quality and Operational Performance of Service Organizations: An Empirical Analysis Using Repeated Cross-Sectional Data of U.S. Firms - Mahour Parast (16904646) (2022)
Research in quality management has provided new insights and directions on how to incorporate quality principles into organizational, operational, and policy decisions. However, most research into quality management has focused on manufacturing firms, which differ from service organizations in their structural and organizational characteristics, thus limiting the value of the findings for service organizations and highlighting the need for further research to assess quality practices in service organizations. In addition, whether quality management practices can provide sustainable quality results for service organizations is overlooked in the literature, primarily due to the lack of availability of reliable and valid data. This had led to inconsistent research findings, which limits theory development and managerial relevance of quality management for service organizations. Building upon the contingency theory of quality management, we examine the determinants of quality results in service organizations and determine the magnitude of the impacts of quality excellence programs on customer satisfaction and operational results in service organizations on a more detailed level. We use repeated cross-sectional data of 16 years from the Baldrige Quality Award program. The results show that information, analysis, and knowledge management is a significant predictor of quality and operational results, and management of process quality and human resource (HR) management significantly influence customer focus and satisfaction, controlling for the firms’ year. We also find that HR management has the strongest impact on customer focus and satisfaction in service organizations, followed by the management of process quality . In addition, the quality and operational improvements resulting from quality management implementation diminish over time in service enterprises. This article provides insights for service organizations and policymakers to enhance service quality and operational performance in service organizations. Other Information Published in: IEEE Transactions on Engineering Management License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/tem.2021.3107499